2021
DOI: 10.1016/j.ejphar.2020.173706
|View full text |Cite
|
Sign up to set email alerts
|

Functional evidence for biased inhibition of G protein signaling by YM-254890 in human coronary artery endothelial cells

Abstract: G protein-coupled receptor (GPCR) has been the primary therapeutic targets for many diseases. Agonists and antagonists of various GPCR are estimated to occupy approximately 35% of the drug market (1). Extracellular signals perceived by GPCR are transmitted via G proteins and trigger intracellular signaling cascades resulting in a plethora of physiological responses. G proteins usually are categorized into four main classical subfamilies according to their α subunits: Gαq/11, Gαs, Gαi/o, Gα12/13 (2). Main subun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 22 publications
1
22
1
Order By: Relevance
“…In line with the findings from Peng et al . , who reported YM depression of cAMP production by several G s PCR in human coronary artery endothelial cells ( 65 ), FR and YM diminished cAMP elevation by the Gs-sensitive V2 vasopressin receptor in HEK293 cells ( Fig. 5 B ).…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…In line with the findings from Peng et al . , who reported YM depression of cAMP production by several G s PCR in human coronary artery endothelial cells ( 65 ), FR and YM diminished cAMP elevation by the Gs-sensitive V2 vasopressin receptor in HEK293 cells ( Fig. 5 B ).…”
Section: Resultsmentioning
confidence: 66%
“…We and others ( 64 , 124 ) recently reported that Gi-Ca 2+ is also fully blocked when cells are pretreated with FR or YM. FR sensitivity of Gi-βγ-Ca 2+ but not of Gi-mediated cAMP lowering has led some authors to hypothesize that FR and YM might inhibit Gβγ signaling as well ( 64 , 65 ). However, this finding may be subject to alternative interpretation (FR inhibits Gβγ versus Gq is required for Gi-Gβγ-calcium), which is why we previously investigated the molecular mechanism whereby this inhibition occurred ( 124 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Ca 2+ nuc is not due to osmolarity or pH. To confirm GPCR involvement, broad-range G protein inhibitor YM-254890 [27] or phospholipase C (PLC) inhibitor U73122 blocked both Ca 2+ i and Ca 2+ nuc ( Fig. 1G-J ).…”
Section: Resultsmentioning
confidence: 94%